The Examination activity of salam leaf ethanolic ekstract (Syzygium polyanthum)[Wight] in mice: The examination activity of salam leaf ethanolic ekstract (Syzygium polyanthum)[Wight] in mice - Shinta Mayasari; Wima Anggitasari; Nafisah Isnawati (Health Media, 2020)
The examination effect of salam leaf ethanolic extract where the purposed of this study was to determine the effect and concentration of salam leaves as antidiarrheals. Ethanol extract dosages of salam leaf given orally (mg/kgbw) was 15;20;25;30;and 35, carried out abservations on mice starting diarrhea, weight of faeces, frequency diarrhea, and the duration of diarrhea for 5 hours. Loperamide HCl given dose of 1 mg/kg is used comparison with negative control CMC-Na, and comparison of Loperamide HCl was the 56th minute, 57,3; 57,9; 59; 58; 64,3 ; 54,3. Stool weight obtained an average of 0,34; 0,35; 0,32; 0,25; 0,27; 0,53; 0,21. The frequency of diarrhea was 8,8; 8,6; 8,9; 9,3; 8,6; 11,2; 8,5. Onset of diarrheal was average of minutes was 206,8; 207,6 ; 209,2; 209; 206,2; 230 and 88. From the research results obtained ethanol extract salam leaves given antidiarrheal effects with an optimum dose of 35mg/kgbw.